Effect of altitude training on sea level aerobic and anaerobic power of elite athletes - Rusko, H. H.; Kirvesniemi, H.; Paavolainen, L.; Vahasoyrinki, P.; Kyro, K. P. (Medicine & Science in Sports & Exercise, 1996)
Maximal oxygen uptake (VO2max) and training pace are decreased in elite athletes at mild and moderate altitude. Skiers (N = 14) trained and raced for 18-28 days at altitude (1,600-1,800 m) and seven skiers trained and raced at sea-level. It was concluded that in elite endurance athletes sea-level VO2max was unchanged and anaerobic power was decreased after moderate altitude training probably due to enhanced stress and decreased training pace at altitude. Implication: Altitude training does not enhance physiological response measures associated with oxygen transport or anaerobic power in elite athletes (skiers). It would be incorrect to justify "benefits" from altitude training in terms of those capacities.